300 Correlation of surgeon radiology assessment with laparoscopic disease site scoring in patients with advanced ovarian cancer. (18th September 2019) - Fleming, N; Westin, S; Meyer, L; Rauh-Hain, A; Shafer, A; Onstad, M; Cobb, L; Fellman, B; Bevers, M; Zand, B; Jazaeri, A; Levenback, C; et al.
Abstract : Objectives: To determine the correlation between surgeon radiology assessment with laparoscopic scoring in patients with newly diagnosed advanced ovarian cancer. Methods: Following IRB approval, 14 gynecologic oncology surgeons from a single institution performed a blinded review of radiology imaging from 20 patients with advanced ovarian cancer. All patients previously underwent laparoscopic scoring using a validated scoring method from April 2013 to December 2017. Surgeons viewed contrasted CT imaging reports and images in a blinded fashion and recorded PIV scores using the validated scoring method. Linear mixed models (LMM) were conducted to calculate the correlation between radiology and laparoscopic score for each surgeon and the group, and the inter-class correlation (ICC) was calculated. Results: The kappa inter-rater agreement was −0.017 (95% CI 0.023 to −0.005), indicating low inter-rater agreement between radiology and actual laparoscopic score. The ICC was 0.06 (0.02–0.21), indicating that surgeons do not score the same across all images. When using a PIV cutoff of 8, the probability of agreement between radiology and actual laparoscopic score was 0.56 (95% CI 0.49–0.73). When looking at disease site subscales, the probability of agreement was (95% CI): peritoneum 0.57 (0.51–0.62), diaphragm 0.54 (0.48–0.60), mesentery 0.51 (0.45–0.57), omentum 0.61 (0.55–0.67), bowel 0.54 (0.44–0.64), stomach 0.71 (CI 0.65–0.76), and liver 0.36 (CI 0.31–0.42). Conclusions: Surgeon radiology review did not highly correlate with actual laparoscopy findings. By subscale, the best agreement is seen when evaluating for stomach involvement, and the worst with liver involvement. Our study highlights the benefits of laparoscopic assessment to determine resectability over radiology alone.